How organizational support enhances organizational citizenship behavior? The mediation role of psychological capital and job satisfaction - Lista Meria; Mira Kartika Dewi Djunaedi; Saukani Saukani; Naning Putri Utami (Jurnal Fokus Manajemen Bisnis, 2025)
The entry of generation Z into the workforce poses new problems in understanding their organizational citizenship behavior, which is affected by the values, expectations, and unique qualities they bring. The complex connection between individual and organizational elements produces a unique ecology where generation Z organizational citizenship behavior thrives, prompting enterprises to modify their strategies. A solid grasp of generation Z organizational citizenship behavior is vital for organizations to optimize their contributions beyond formal responsibilities and increase overall organizational effectiveness. By analyzing the effects of psychological capital, job satisfaction, and organizational support on generation Z workers, this study aims to investigate the factors that affect organizational citizenship behavior. Data was obtained from a survey of 276 respondents randomly selected from various industries in Jakarta, Indonesia. The research data were processed and examined using SEM. The studies revealed that job satisfaction, psychological capital, and organizational support are the primary factors influencing generation Z employees' higher organizational citizenship behavior. Further research on mediation found that psychological capital and job satisfaction mediated the relationship between organizational support and organizational citizenship behavior. This study advances the topic of organizational behavior and management. In this regard, it assists organizations in creating guidelines and policies to enhance organizational citizenship behavior through psychological capital, job satisfaction, and organizational support.